2009
DOI: 10.1002/art.24265
|View full text |Cite
|
Sign up to set email alerts
|

In vitro stage‐specific chondrogenesis of mesenchymal stem cells committed to chondrocytes

Abstract: Objective. Osteoarthritis is characterized by an imbalance in cartilage homeostasis, which could potentially be corrected by mesenchymal stem cell (MSC)-based therapies. However, in vivo implantation of undifferentiated MSCs has led to unexpected results. This study was undertaken to establish a model for preconditioning of MSCs toward chondrogenesis as a more effective clinical tool for cartilage regeneration.Methods. A coculture preconditioning system was used to improve the chondrogenic potential of human M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 49 publications
4
118
0
1
Order By: Relevance
“…In recent years, a number of studies have demonstrated chondrocyte-mediated chondrogenic differentiation of stem cells [36,[41][42][43]. A variety of unidentified morphogenetic factors from chondrocytes such as growth factors, hormones, and ECM influence the chondrogenesis of LVEC cells either individually or in synergy with other factors such as TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies have demonstrated chondrocyte-mediated chondrogenic differentiation of stem cells [36,[41][42][43]. A variety of unidentified morphogenetic factors from chondrocytes such as growth factors, hormones, and ECM influence the chondrogenesis of LVEC cells either individually or in synergy with other factors such as TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…Coculturing chondrocytes together with MSCs takes advantage of both secreted factors and direct cell-to-cell contact to direct differentiation and potentially stimulate matrix production. [28][29][30] The objective of this study was to determine the optimal ratio of chondrocytes to MSCs that results in dense and well-distributed cartilage-like ECM deposition within a fibrous polymeric scaffold, while minimizing the required number of chondrocytes. This was performed by culturing in fetal bovine serum (FBS) containing media without exogenous growth factor supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this in vitro culture system made MSCs fate more controllable than in vivo and easier for understanding the molecular events within the crosstalk of MSCs and the local environment. Co-culturing with appropriate cell types, MSCs have been elucidated to commit to corresponding lineages, such as osteoblasts (Csaki et al 2009), chondrocytes (Chen et al 2009), ligament cells (Lee et al 2007), cardiomyocytes , hepatocytes (Lange et al 1999) and smooth muscle cells Ball et al 2004). Interestingly, direct cell-to-cell contact has been proven to be indispensable for the commitment of a sort of cell types, such as smooth muscle cells and cardiomyocytes Ball et al 2004).…”
Section: Introductionmentioning
confidence: 99%